2011
DOI: 10.1029/2011gl047314
|View full text |Cite
|
Sign up to set email alerts
|

Compositional diversity at Theophilus Crater: Understanding the geological context of Mg-spinel bearing central peaks

Abstract: [1] Analysis of high resolution Moon Mineralogy Mapper (M 3 ) data reveals the presence of a prominent Mg-spinel-rich lithology in the central peaks of Theophilus crater on the lunar nearside. Other peak-associated lithologies are comprised of plagioclase, olivine, and pyroxene-bearing materials. A consistent spatial association of Mg-spinel with mafic-free anorthosite is recognized. Documentation of Theophilus central peaks brings the global inventory of Mg-spinel-rich lithology to two widely separated occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(42 citation statements)
references
References 16 publications
2
40
0
Order By: Relevance
“…The Mg-rich lithologies seen at both Moscoviense and Theophilus (Fig. 15) occur as discrete small areas, all within a highly feldspathic matrix Dhingra et al 2011;Lal et al 2012). Furthermore, at the best scale currently available (~140 m), no two mafic crustal lithologies discussed here have yet been detected in a contiguous manner to suggest layering.…”
Section: Layering Within the Lunar Highlands And Mg-suitementioning
confidence: 71%
See 1 more Smart Citation
“…The Mg-rich lithologies seen at both Moscoviense and Theophilus (Fig. 15) occur as discrete small areas, all within a highly feldspathic matrix Dhingra et al 2011;Lal et al 2012). Furthermore, at the best scale currently available (~140 m), no two mafic crustal lithologies discussed here have yet been detected in a contiguous manner to suggest layering.…”
Section: Layering Within the Lunar Highlands And Mg-suitementioning
confidence: 71%
“…16, red square) has an inferred Mg# > 75, is located within the Procellarum KREEP Terrane (Jolliff et al 2000), and is associated with a localized thorium enhancement on the order of 16.5 ±2.5 ppm . Dhingra et al (2011) identified a distinct Mg-suite mineralogy, possibly a pink spinel anorthosite within the central peak of Theophilus Crater (Fig. 16).…”
Section: Global Distribution Of the Mg-suitementioning
confidence: 99%
“…These combined technological improvements have allowed the SELENE Spectral Profiler and Multiband Imager (MI) and the Chandrayaan‐1 Moon Mineralogy Mapper (M 3 ) to unambiguously identify Fe‐bearing crystalline plagioclase across the lunar surface based on its unique 1.25 µm absorption band [ Burns , , ; Adams and McCord , ; Adams and Goullaud , ]. Pure crystalline plagioclase has now been identified in widespread locations across the lunar surface: around impact basins, in massifs in the Inner Rook Mountains of Orientale, and in the central peaks, walls, floor, and ejecta of craters [ Matsunaga et al , ; Ohtake et al , ; Pieters et al , ; Dhingra et al , ; Donaldson Hanna et al , ; Yamamoto et al , ; Cheek et al , ]. While previous NIR laboratory studies have suggested that the band depth and center position of the 1.25 µm feature may vary with Fe and An contents [ Bell and Mao , ; Adams and Goullaud , ; Cheek et al , , ], the relationship between NIR spectral properties of plagioclase and its composition (An#) has yet to be quantified.…”
Section: Introductionmentioning
confidence: 99%
“…Lucey [] used a nonlinear radiative transfer technique to illustrate that NIR spectra assumed to be shocked plagioclase from Orientale [ Spudis et al , ] could be modeled with either crystalline anorthite plus npFe 0 or shocked anorthite and get similar spectral results. Thus, to uniquely distinguish shocked plagioclase outcrops from space weathered soils, additional information such as albedo and the geologic context should be explored using high spatial resolution imagery like the Lunar Reconnaissance Orbiter Camera or the Kaguya Terrain Camera [ Dhingra et al , ]. To avoid the ambiguity between shocked versus weathered regions, our study focuses only on regions that clearly exhibit the 1.25 µm absorption band resulting from minor amounts of Fe 2+ in crystalline plagioclase and are unambiguously rich in Fe‐bearing plagioclase.…”
Section: Introductionmentioning
confidence: 99%
“…The M 3 data with high spectral resolution and wide spectral coverage identified sites showing Mg-spinel anorthosite (devoid of olivines and pyroxenes and having FeO < 5 wt%) along the rings of Moscoviense basin on the far side of the Moon [54]. These were also found in the central peak of Theophilus crater along the ring of Nectaris basin [55,56].…”
Section: Mg-spinel Anorthosite Across the Moonmentioning
confidence: 94%